Public entrepreneurship, citizenship, and self-governance - Aligică, Paul Dragoş 1966- (Cambridge studies in economics, choice, and society, 2019)
In this book Paul Dragos Aligica revisits the theory of political self-governance in the context of recent developments in behavioral economics and political philosophy that have challenged the foundations of this theory. Building on the work of the 'Bloomington School' created by Nobel Laureate Elinor Ostrom and Public Choice political economy co-founder Vincent Ostrom, Aligica presents a fresh conceptualization of the key processes at the core of democratic-liberal governance systems involving civic competence and public entrepreneurship. The result is not only a re-assessment and re-articulation of the theories constructed by the Bloomington School of Public Choice, but also a new approach to several cutting-edge discussions relevant to governance studies and applied institutional theory, such as the debates generated by the recent waves of populism, paternalism and authoritarianism